Giant Cell Tumor of Bone, Tendon, and Soft Tissue: Pathogenesis and Clinical Manifestations - Yulianti, Arwinda Febri; Paerdoe, Lalu Dane Pemban; Hidayat, Rahmat; Qindi, Ahmad Sa`bi Al; Hadinata, Lalu Gde Gilang Alid; Widad, Najwa; Febianisa, Tabitha Afifah; Pramesti, Evane Dyahayu; Khairifathiyyah, Khairifathiyyah; Amalia, Azka; Purnaning, Dyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Giant Cell Tumor (GCT) is a primary neoplasm that is intermediate malignant, characterized by aggressive local growth and the possibility of metastasis, especially to the lungs. Giant Cell Tumor (GCT) occurs in bones, tendons, and soft tissues. The purpose of this literature study is to identify differences in GCT manifestations in various anatomical locations, evaluate risk factors that contribute to tumor growth and recurrence, and assess the effectiveness of various therapeutic modalities that have been used, both conservative and operative. The method used is a literature study by reviewing various scientific journals obtained from the database. The findings show that Giant Cell Tumor (GCT) is a group of neoplasms that are histologically similar but have different clinical, molecular characteristics, and anatomical locations, including GCT in bones (GCTB), tendons (GCTTS), and soft tissues (GCTST). Although generally classified as benign, GCT can be locally aggressive with a risk of recurrence and in some cases is capable of metastasis, especially to the lungs. GCTB is most commonly found in the long bones of individuals aged 20–40 years and is characterized by the H3F3A mutation, which is an important diagnostic marker. GCTTS, which originates in the synovium, is more common in women aged 30–50 years and shows increased CSF1 expression due to a genetic translocation.